2001
DOI: 10.1093/oxfordjournals.molbev.a003893
|View full text |Cite
|
Sign up to set email alerts
|

Selection Against Deleterious LINE-1-Containing Loci in the Human Lineage

Abstract: We compared sex chromosomal and autosomal regions of similar GC contents and found that the human Y chromosome contains nine times as many full-length (FL) ancestral LINE-1 (L1) elements per megabase as do autosomes and that the X chromosome contains three times as many. In addition, both sex chromosomes contain a ca. twofold excess of elements that are >500 bp but not long enough to be capable of autonomous replication. In contrast, the autosomes are not deficient in short (<500 bp) L1 elements or SINE elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
133
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 45 publications
14
133
1
Order By: Relevance
“…Although these observations are also consistent with several alternative hypotheses (e.g. accumulation of deleterious insertions due to decreased selection efficiency within these regions) that do not necessitate ectopic recombination, there is increasing support from the drosophila model for significant selection against TE loci due to their potential for instability [5] Recent data from humans, showing stronger selection against full-length L1 elements than their truncated counterparts, is also highly suggestive of selection against ectopic recombination instability in our own lineage [6], particularly when taken together with an earlier genomic analysis of TE accumulation on human sex chromosomes which indicated that negative selection on L1s was related to L1 insertion size [7] as opposed to the full length vs. non-full length status of insertions. In the latter work, a statistically significant accumulation of >500bp but less-thanfull-length L1 inserts on the human sex chromosomes vs. the autosomes [7].…”
Section: Introductionmentioning
confidence: 63%
“…Although these observations are also consistent with several alternative hypotheses (e.g. accumulation of deleterious insertions due to decreased selection efficiency within these regions) that do not necessitate ectopic recombination, there is increasing support from the drosophila model for significant selection against TE loci due to their potential for instability [5] Recent data from humans, showing stronger selection against full-length L1 elements than their truncated counterparts, is also highly suggestive of selection against ectopic recombination instability in our own lineage [6], particularly when taken together with an earlier genomic analysis of TE accumulation on human sex chromosomes which indicated that negative selection on L1s was related to L1 insertion size [7] as opposed to the full length vs. non-full length status of insertions. In the latter work, a statistically significant accumulation of >500bp but less-thanfull-length L1 inserts on the human sex chromosomes vs. the autosomes [7].…”
Section: Introductionmentioning
confidence: 63%
“…Regardless of whether Alu elements are beneficial or merely tolerated, the increased abundance of Alu elements around housekeeping genes stood in stark contrast to the scarcity of longer (>400-bp) repeats and repeat tracts (LINE-1 elements and various other repeats) in these same regions Although, the lower abundance of the TT|AAAA target sequence near housekeeping genes may very well contribute to LINE-1 scarcity (Jurka, 1997;Cost and Boeke, 1998;Lander et al, 2001;Graham and Boissinot, 2006) despite their otherwise random insertion pattern (Smit, 1999;Boissinot et al, 2001;Lander et al, 2001;Ovchinnikov et al, 2001;Gilbert et al, 2002;Myers et al, 2002;Symer et al, 2002;Szak et al, 2002;Jurka et al, 2004;Gilbert et al, 2005), at least one additional explanation is needed since long repeats in general were scarce. One reason why long repeats might be selected against near housekeeping genes is that an abundance of these repeats might reduce gene expression via heterochromatin spread.…”
Section: Long Repeats May Be Disadvantageous To Nearby Housekeeping Gmentioning
confidence: 99%
“…Alu transposons differ from other SINEs in that they are not derived from tRNA genes, but rather from the 7SL RNA gene (Ullu and Tschudi, 1984;Quentin, 1994;Smit, 1996;Okada and Hamada, 1997;Terai et al, 1998;Lander et al, 2001) which encodes the RNA component of the signal recognition particle that mediates the translocation of nascent secretory and membrane proteins (Wild et al, 2004). Aside from favoring TT|AAAA target sequences (Feng et al, 1996;Jurka, 1997;Cost and Boeke, 1998), human Alu and LINE-1 elements have been reported to insert at random positions in the genome (Smit, 1999;Boissinot et al, 2001;Lander et al, 2001;Ovchinnikov et al, 2001;Gilbert et al, 2002;Myers et al, 2002;Symer et al, 2002;Szak et al, 2002;Jurka et al, 2004;Gilbert et al, 2005). However, there is some evidence for insertional hot spots (Cost and Boeke, 1998;Myers et al, 2002;Graham and Boissinot, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To complete integration, the second strand of host DNA must be cleaved, RNA removed, the newly synthesized strand copied, and breaks resolved. The mechanism by which these later steps are accomplished is only beginning to be understood, with recent biochemical data from a related non-LTR retrotransposon R2 of the silkmoth, Bombyx mori, suggesting that a second R2 protein is involved in cleavage, RNA displacement, and synthesis of the second strand (Bibillo and Eickbush 2002a; Christensen and Eickbush 2005).Following essentially random integration, endogenous L1s are thought to be lost over time due to strong negative selection leading to their uneven genomic distribution (Boissinot et al 2001(Boissinot et al , 2004Ovchinnikov et al 2001;Medstrand et al 2002). This is reflected in their overrepresentation in GC-poor genomic regions (Lander et al 2001;Ovchinnikov et al 2001;Boissinot et al 2004), under-representation within 5 kb of genes (Medstrand et al 2002), and the selective loss of longer (>500 bp) L1s from recombining regions of the genome (Boissinot et al 2001).…”
mentioning
confidence: 99%